Sidik Jari KLT dan Evaluasi Aktivitas Inhibisi Xantin Oksidase Ekstrak Etanol Sidaguri (Sida rhombifolia) Berdasarkan Umur Tanam Berbeda - Ade Heri Mulyati; Tamimah Shafwatul Ishlah; Dea Silviani; Taopik Ridwan; Auliya Ilmiawati; Alfi Hudatul Karomah; Mohamad Rafi (Universitas Tidar, 2025)
Sidaguri (Sida rhombifolia) belongs to the family Malvaceae and is used in traditional medicine to treat skindiseases, diarrhea, malaria, fever, and gout. These activities are caused by the presence of bioactivemetabolites, such as alkaloids, flavonoids, steroids, tannins, and saponins. Several factors, including harvestage, could affect the metabolite composition and concentration in a plant. In this study, the TLC fingerprint ofS. rhombifolia at planting ages of 3, 4, and 5 months was determined and in vitro xanthine oxidase inhibitoryactivity was evaluated. The TLC fingerprints obtained from the three planting ages had similar patterns. Thereare 11 compound bands with different color intensities at each planting age. Principal component analysis candifferentiate S. rhombifolia by planting age using TLC fingerprint analysis, with a total PC of 99%. The resultsof xanthine oxidase inhibition showed that the S. rhombifolia ethanol extract at 3, 4, and 5 months of plantingage inhibited the enzyme activity, with percent inhibitions of 45.37%, 44.72%, and 6.87%, respectively, at aconcentration of 100 ppm. Different planting ages of sidaguri are thought to contain varying concentrationsof compounds, as indicated by TLC fingerprints, and to result in different levels of xanthine oxidase inhibition. Kata kunci: sidaguri, TLC fingerprints, PCA, xanthine oxidase